Application of the Rochester Criteria to Identify Febrile Infants With Bacteremia and Meningitis. Issue 1 (January 2019) - Aronson, Paul L.; McCulloh, Russell J.; Tieder, Joel S.; Nigrovic, Lise E.; Leazer, Rianna C.; Alpern, Elizabeth R.; Feldman, Elana A.; Balamuth, Fran; Browning, Whitney L.; Neuman, Mark I.
Abstract : Objectives: The Rochester criteria were developed to identify febrile infants aged 60 days or younger at low-risk of bacterial infection and do not include cerebrospinal fluid (CSF) testing. Prior studies have not specifically assessed criteria performance for bacteremia and bacterial meningitis (invasive bacterial infection). Our objective was to determine the sensitivity of the Rochester criteria for detection of invasive bacterial infection. Methods: Retrospective cohort study of febrile infants aged 60 days or younger with invasive bacterial infections evaluated at 8 pediatric emergency departments from July 1, 2012, to June 30, 2014. Potential cases were identified from the Pediatric Health Information System using International Classification of Diseases, Ninth Revision diagnosis codes for bacteremia, meningitis, urinary tract infection, and fever. Medical record review was then performed to confirm presence of an invasive bacterial infection and to evaluate the Rochester criteria: medical history, symptoms or ill appearance, results of urinalysis, complete blood count, CSF testing (if obtained), and blood, urine, and CSF culture. An invasive bacterial infection was defined as growth of pathogenic bacteria from blood or CSF culture. Results: Among 82 febrile infants aged 60 days or younger with invasive bacterial infection, the sensitivity of the Rochester criteria were 92.7% (95% confidence interval [CI], 84.9%–96.6%) overall, 91.7% (95% CI, 80.5%–96.7%) for neonates 28 days or younger, and 94.1% (95% CI, 80.9%–98.4%) for infants aged 29 to 60 days old. Six infants with bacteremia, including 1 neonate with bacterial meningitis, met low-risk criteria. Conclusions: The Rochester criteria identified 92% of infants aged 60 days or younger with invasive bacterial infection. However, 1 neonate 28 days or younger with meningitis was classified as low-risk. Abstract : Supplemental digital content is available in the text.